Lack of FcRn Impairs Natural Killer Cell Development and Functions in the Tumor Microenvironment - Castaneda, Diana Cadena; Dhommée, Christine; Baranek, Thomas; Dalloneau, Emilie; Lajoie, Laurie; Valayer, Alexandre; Arnoult, Christophe; Demattéi, Marie-Véronique; Fouquenet, Delphine; Parent, Christelle; Heuzé-Vourc'h, Nathalie; Gouilleux-Gruart, Valérie (Frontiers in Immunology, 2018)
The neonatal Fc receptor (FcRn) is responsible for the recycling and transcytosis of IgG and albumin. FcRn level was found altered in cancer tissues and implicated in tumor immuno-surveillance and neoplastic cell growth. However, the consequences of FcRn down-regulation in the anti-tumor immune response are not fully elucidated. By using the B16F10 experimental lung metastasis model in an FcRn-deficient microenvironment (FcRn-/- mice), we found lung metastasis associated with an abnormal natural killer (NK) cell phenotype. In FcRn-/- mice, NK cells were immature, as shown by their surface marker profile and their decreased ability to degranulate and synthesize interferon γ after chemical and IL-2 or IL-12, IL-15 and IL-18 activation. These new findings support the critical role of FcRn downregulation in the tumor microenvironment in anti-tumor immunity, via NK cell maturation and activation.